Orchard Algorithm (OA): A new meta-heuristic algorithm for solving discrete and continuous optimization problems - Kaveh, Mehrdad; Mesgari, Mohammad Saadi; Saeidian, Bahram (Mathematics and computers in simulation, 2023)
Meta-heuristic algorithms have been widely used to solve different optimization problems. There have always been ongoing efforts to develop new and efficient algorithms. In this paper, the Orchard Algorithm (OA) is designed and introduced, inspired by fruit gardening. In this process, various actions such as irrigation, fertilization, trimming, and grafting lead to a fruit orchard where most trees grow and produce fruit adequately. In OA, both explorations of the search space and exploitation of the best solutions are achieved using personal and social behavior. By introducing various operators such as annual growth, screening, and grafting, the algorithm can efficiently search and explore the search space. The performance of the proposed OA algorithm was evaluated on CEC2005, IEEE CEC06 2019,test functions, and five real-world engineering problems compared with 13 widely used and competitive algorithms. Thirty benchmark functions were used to compare the capabilities of the OA algorithm with other research. The OA yields far better results in many aspects than the other algorithms. The results show the OA’s superiority and this algorithm’s capability in solving optimization problems. •We proposed new meta-heuristic algorithm for solving optimization problems.•The orchard algorithm is introduced, which is inspired by fruit gardening process.•In OA, using personal and social behavior, exploration and exploitation are achieved.•At 60 test functions, OA performed better than other algorithms.•The orchard algorithm performed very well in five engineering benchmark problems.